Antibacterial Efficacy of Herbal and 0.2% Chlorhexidine Mouth Rinse Against Oral Pathogens - An In vitro Study - Palaneeswaran Kamalashankar; Nalankilli Ashok Viswanath; Nyklesh V; Mani Muralimani; Aziz Mac B Abdul (Wolters Kluwer Medknow Publications, 2024)
BackgroundNature has given us an enormous number of medicines for every disease that affects people. AimTo compare the antimicrobial efficacy of an herbal and 0.2% chlorhexidine gluconate mouthrinse against Streptococcus mutans, Staphylococcus aureus, and Enterococcus faecalis. Materials and MethodsThe antimicrobial effectiveness (zone of inhibition) of a herbal mouthrinse and 0.2% chlorhexidine mouthrinse were determined by agar well-diffusion method. ResultsAt 50% concentration, the experimental mouthrinse inhibits the growth of Streptococcus mutans, Staphylococcus aureus, and Enterococcus faecalis. ConclusionAgainst the three strains, chlorhexidine mouthrinse (0.2%) performs better in terms of antimicrobial effectiveness.